2002
DOI: 10.1038/nsb814
|View full text |Cite
|
Sign up to set email alerts
|

A new family of plant transcription factors displays a novel ssDNA-binding surface

Abstract: The crystal structure of p24, the single-stranded DNA (ssDNA) binding subunit of the plant defense transcription factor PBF-2, has been determined to 2.3 A resolution. p24 is representative of a novel family of ubiquitous plant-specific proteins that we refer to as the Whirly family because of their quaternary structure. PBF-2 is composed of four p24 molecules that interact through a helix-loop-helix motif. This interaction produces a central pore, with beta-strands radiating outwards, resulting in a whirligig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 36 publications
6
111
0
2
Order By: Relevance
“…The data were processed, indexed and scaled using either HKL-2000 (Otwinowski & Minor, 1997) or XDS (Kabsch, 2010) and SCALA (Evans, 1993). The structures of WHY1 and WHY2 were solved by molecular replacement using PHENIX (Adams et al, 2010) with the crystal structures of the potato WHY1 (PDB entry 1l3a; Desveaux et al, 2002) and WHY2 (PDB entry 3n1h; Cappadocia et al, 2010) as search models, respectively. The structure of WHY3 was also solved by molecular replacement using the refined structure of WHY1 as a search model.…”
Section: X-ray Data Collection Structure Determination and Refinementmentioning
confidence: 99%
See 2 more Smart Citations
“…The data were processed, indexed and scaled using either HKL-2000 (Otwinowski & Minor, 1997) or XDS (Kabsch, 2010) and SCALA (Evans, 1993). The structures of WHY1 and WHY2 were solved by molecular replacement using PHENIX (Adams et al, 2010) with the crystal structures of the potato WHY1 (PDB entry 1l3a; Desveaux et al, 2002) and WHY2 (PDB entry 3n1h; Cappadocia et al, 2010) as search models, respectively. The structure of WHY3 was also solved by molecular replacement using the refined structure of WHY1 as a search model.…”
Section: X-ray Data Collection Structure Determination and Refinementmentioning
confidence: 99%
“…The crystal structures of the Solanum tuberosum (potato) WHY1 and WHY2 proteins were solved in the free form (Desveaux et al, 2002;Cappadocia et al, 2008Cappadocia et al, , 2010. These structures revealed that both chloroplast-directed and mitochondria-directed Whirly proteins assemble into tetramers with C4 symmetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that this protein might bind to melted promoter regions to modulate transcriptional activities. The interaction of StWHY1 with the PR-10a promoter was mapped to a region termed the elicitor response element (ERE) for elicitor-induced gene expression (Després et al, 1995;Desveaux et al, 2000Desveaux et al, , 2002. The Arabidopsis genome encodes three WHY proteins: AtWHY1 and AtWHY3 contain plastid-targeting signal, whereas AtWHY2 localizes to mitochondria (Krause et al, 2005).…”
mentioning
confidence: 99%
“…Analyses of the crystal structure of WHIRLY proteins revealed that they form tetramers [68] and that these tetramers can also assemble into 24-mers [69,70]. The 24-oligomers of WHIRLY1 have been isolated from chloroplasts [70] and they are likely to be the structures that bind to the thylakoids.…”
Section: The Whirly Family Of Proteinsmentioning
confidence: 99%